2021
DOI: 10.3389/fmars.2021.769908
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Commercialization of Endangered Sharks and Rays (Elasmobranchii) Along the Coastal Amazon as Revealed by DNA Barcode

Abstract: Elasmobranchs represent a well-defined group, composed of about 1,150 species inhabiting diverse aquatic environments. Currently, several of these species have been classified as threaten due to overexploitation. Therefore, we used DNA barcode to identify traded species of sharks and stingrays in the municipality of Bragança (Amazon coastal region), a major fishery landing site in northern Brazil. We collected a total of 127 samples labeled into 24 commercial nomenclatures over 1-year period. Twenty species we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This shark is the most frequently exploited among the Sphyrnidae family and ranks fourth most commonly found and sampled species (Feitosa et al 2018). Genus Sphyrna identified in the present study are threatened with extinction (Martins et al 2021). According to fishermen's information, the waters of Faekhuna'a served as a habitat for hammerhead sharks and was a primary catch zone.…”
Section: Conservation Statusmentioning
confidence: 69%
“…This shark is the most frequently exploited among the Sphyrnidae family and ranks fourth most commonly found and sampled species (Feitosa et al 2018). Genus Sphyrna identified in the present study are threatened with extinction (Martins et al 2021). According to fishermen's information, the waters of Faekhuna'a served as a habitat for hammerhead sharks and was a primary catch zone.…”
Section: Conservation Statusmentioning
confidence: 69%
“…In an analysis of sharks sold in the fish market in Braganca, an important fishing port in Parástate, Martins et al (2021) identified 11 taxa of the orders Orectolobiformes and Carcharhiniformes, of which, eight are classified as endangered. Clearly, then, the generic classification of catches by their vernacular names does not reflect the true diversity of the impacted fauna, and limit the more effective analysis of the dynamics of existing stocks and their response to fishing pressure, whether targeted specifically or indirectly, as bycatch (Davidson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The use of molecular genetics as a tool in forensics and for the certification of commercial products has proven to be highly efficient in solving fraud cases or substituting seafood products [ 7 , 53 ]. For instance, several reports based on genetic data of commercialized fish products have identified endangered species [ 7 , 54 ], providing helpful information about the illegal trade of species threatened with extinction [ 55 ].…”
Section: Discussionmentioning
confidence: 99%